Generation of Porcine Induced Neural Stem Cells Using the Sendai Virus - Chakritbudsabong, Warunya; Sariya, Ladawan; Jantahiran, Phakhin; Chaisilp, Nattarun; Chaiwattanarungruengpaisan, Somjit; Rungsiwiwut, Ruttachuk; Ferreira, Joao N.; Rungarunlert, Sasitorn (Frontiers in Veterinary Science, 2022)
The reprogramming of cells into induced neural stem cells (iNSCs), which are faster and safer to generate than induced pluripotent stem cells, holds tremendous promise for fundamental and frontier research, as well as personalized cell-based therapies for neurological diseases. However, reprogramming cells with viral vectors increases the risk of tumor development due to vector and transgene integration in the host cell genome. To circumvent this issue, the Sendai virus (SeV) provides an alternative integration-free reprogramming method that removes the danger of genetic alterations and enhances the prospects of iNSCs from bench to bedside. Since pigs are among the most successful large animal models in biomedical research, porcine iNSCs (piNSCs) may serve as a disease model for both veterinary and human medicine. Here, we report the successful generation of piNSC lines from pig fibroblasts by employing the SeV. These piNSCs can be expanded for up to 40 passages in a monolayer culture and produce neurospheres in a suspension culture. These piNSCs express high levels of NSC markers (PAX6, SOX2, NESTIN, and VIMENTIN) and proliferation markers (KI67) using quantitative immunostaining and western blot analysis. Furthermore, piNSCs are multipotent, as they are capable of producing neurons and glia, as demonstrated by their expressions of TUJ1, MAP2, TH, MBP, and GFAP proteins. During the reprogramming of piNSCs with the SeV, no induced pluripotent stem cells developed, and the established piNSCs did not express OCT4, NANOG, and SSEA1. Hence, the use of the SeV can reprogram porcine somatic cells without first going through an intermediate pluripotent state. Our research produced piNSCs using SeV methods in novel, easily accessible large animal cell culture models for evaluating the efficacy of iNSC-based clinical translation in human medicine. Additionally, our piNSCs are potentially applicable in disease modeling in pigs and regenerative therapies in veterinary medicine.